2015
DOI: 10.1007/s10750-015-2418-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing recent climatic and human influences on chironomid communities from two moderately impacted lakes in western Ireland

Abstract: This study assessed the influences of climate warming and human impacts on Irish lakes over the late nineteenth to early twenty-first centuries. High-resolution chironomid (Insecta: Diptera) stratigraphies were developed for two low-to mid-elevation lakes in northwest Ireland to determine if lakes with mild-to-moderate human impacts can be used to accurately reconstruct mean July air temperature. Application of an Ireland-based chironomid-inference model to quantitatively estimate July air temperature (r 2 jac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Chironomidae sp., which are non-biting midges that act as important indicator organisms, were also found in this study ( Table 2 ). The distribution of this species in freshwater bodies indicates the presence of pollution in the environment, and is useful for the study of past environmental conditions in affected regions ( Francis, 2004 ; MacDonald et al, 2009 ; McKeown & Potito, 2016 ). The relationship between midges and environmental factors can be applied to further our understanding of past environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…Chironomidae sp., which are non-biting midges that act as important indicator organisms, were also found in this study ( Table 2 ). The distribution of this species in freshwater bodies indicates the presence of pollution in the environment, and is useful for the study of past environmental conditions in affected regions ( Francis, 2004 ; MacDonald et al, 2009 ; McKeown & Potito, 2016 ). The relationship between midges and environmental factors can be applied to further our understanding of past environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…The timing and magnitude of changes in the chironomid stratigraphy show that land-use, potentially influenced by climate change (Stolze et al, 2013b), is the main control on the chironomid community at Templevanny Lough during the Neolithic. Although chironomids have been mostly used as a palaeotemperature indicator in the past, as temperature tends to be the main driver behind chironomid community compositional change (Brooks and Birks, 2001), more recent studies have shown that even moderate human impacts are sufficient enough to over-ride the climate signal in the chironomid record (Brodersen and Quinlan, 2006; McKeown and Potito, 2016), which seems to be the case in Templevanny Lough.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of chironomids (non-biting midge, Insecta; Diptera) as a Holocene palaeoclimatic proxy in Ireland has been demonstrated by Potito et al (2014), McKeown and Potito (2016), and Taylor et al (2018. As chironomids can track major and minor changes in temperature through time, independently of precipitation (Eggermont and Heiri, 2012), they have the potential to capture summer air temperature fluctuations inherent to the Irish climate system.…”
Section: Introductionmentioning
confidence: 94%
“…Criticisms suggest that variables other than the one being reconstructed have a negligible effect on abiotic assemblages (Juggins, 2013). To complicate matters further, the chironomid-temperature relationship can be decoupled by non-climate variables such as human activities in the lake catchment (McKeown, 2013;McKeown and Potito, 2016;Taylor et al, 2017;Chique et al, 2018). Pollen can be used as an indicator of human activity through the identification of cereal-type pollen, Plantago sp.…”
Section: Introductionmentioning
confidence: 99%